The Intersection of Tobacco Use, Health Disparities, and Inequalities in Lung Cancer Treatment and Survival - Shankar, Abhishek; Yau, Callum; Wallbridge, Isaac G.; Saini, Deepak; Prasad, Chandra Prakash; Singh, Pritanjali; Kaur, Jagdish; Roy, Shubham; Sinha, Praveen (Indian Journal of Medical and Paediatric Oncology, 2022)
Tobacco use and socioeconomic status are related with each other and important determinants of disparities and inequalities to access to care. There is overall reduction in number of smokers but still most number of smokers is represented by people from low socioeconomic status, with less number of these people having an access to the treatment centers. Patients who are tobacco users have shown to be less likely to receive any form of treatment for lung cancer, whether that be chemotherapy, radiotherapy, or surgery. As there is less awareness about signs and symptoms of lung cancer, lower socioeconomic patients are likely to report to hospitals at advanced stages or many times as a medical emergency. We are well aware that patients with advanced lung cancer have lower chances of survival in view of incomplete response to treatment. As there is an intersection between tobacco use, health disparities, and inequalities and lung cancer treatment and survival, this issue needs better focus and attention to minimize disparities and inequalities in access to care and outcomes.
Keywords: lung cancer; tobacco; smoking; inequalities; health disparities